Marginalia, Value and Meaning: A Study. Issue 3 (2nd October 2017) - Mako, Richard Edward
Abstract: This article looks at the value of marginalia as created by the patrons of the library at Queensborough Community College, City University of New York. The author chose 10 books from different areas of the literature section in the library to provide a variety of samples. This study explores marginalia from the perspective of ordinary library patrons, as opposed to that of famous authors, an aspect of marginalia not often investigated in the literature. This study asks the questions, such as is there anything to be gained from studying marginalia created by ordinary people? and Are there patterns from the data that might suggest how to better serve our patrons?